2018
DOI: 10.1111/jcpt.12719
|View full text |Cite
|
Sign up to set email alerts
|

Probable pulmonary embolism with repeat administration of prothrombin complex concentrate in a factor Xa inhibitor patient

Abstract: Treatment of DOAC-induced bleeding remains an "off-label" indication for PCC. Additional doses should be given with caution if given at all and patients monitored closely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In addition to the lack of clinical benefit, repeat dosing may lead to excessive accumulation of factors and cause a prothrombotic state. Case studies have shown probable thromboembolic complications caused by repeat dosing, especially at doses greater than listed in the package insert 30,31. Finally, repeat dosing is not recommended in the package labeling due to lack of available safety information; however, repeat dosing has been shown to be common in practice and should be evaluated on a case-by-case basis 32…”
Section: Evidence For Pcc Use With Warfarinmentioning
confidence: 99%
“…In addition to the lack of clinical benefit, repeat dosing may lead to excessive accumulation of factors and cause a prothrombotic state. Case studies have shown probable thromboembolic complications caused by repeat dosing, especially at doses greater than listed in the package insert 30,31. Finally, repeat dosing is not recommended in the package labeling due to lack of available safety information; however, repeat dosing has been shown to be common in practice and should be evaluated on a case-by-case basis 32…”
Section: Evidence For Pcc Use With Warfarinmentioning
confidence: 99%